Sou bacharel e sou professor. E agora? A construção do ser professor na educação profissional técnica de nível médio - Lima, Inalda Tereza Sales de (2021)
The present research arose from a personal concern, arising from the long life with bachelors who become teachers in professional education. We investigated the processes in which unlicensed professionals became teachers and how teaching is constituted by them, considering the knowledge constructed in this process. We start from the following research problem: How do bachelor's professionals who work in technical vocational education at high school - EPTNM constitute themselves as teachers? As a general objective, we seek to investigate how and under what circumstances professional bachelors who work in technical vocational education at secondary level are constituted as teachers. The focus of the research was the Academic Department of Infrastructure - DAINFRA of the Instituto Federal do Amazonas - IFAM - Campus Manaus Centro - CMC, responsible for offering the High School Technical Course in Buildings, among others. We start by contextualizing professional education considering its origin, legal bases and theoretical foundations that guide teacher training and teaching knowledge. The methodological path followed the prerogatives of Connelly and Clandinin (1995), and the data analysis was based on comprehensiveinterpretative analysis (SOUZA, 2006). The research, of a qualitative nature, was based on the narrative approach, having as participants six bachelor teachers, who wrote training memorials, in addition to being interviewed following the assumptions of the narrative interview (JOVCHELOVITCH; BAUER, 2014). We found that most bachelors joined the teaching profession because of the job opportunities that were presented to them, in addition to the possibility of sharing knowledge and training new technicians, in addition to personal motivations, such as feeling vocational to teach. They cited former teachers and experiences lived as students as models for their performance as teachers and the importance of exchanging with peers and students. It is also an important reference for teaching, the professional experiences arising from working in the specific area. The bachelors also reported the difficulties experienced in their teaching practice, which led us, together with other points reported by them, to the construction of a Didactic Guide to assist bachelors who are part of teaching. With this research, we hope to subsidize the self-training of bachelor teachers, thus contributing to teacher training for professional education, which still faces many challenges.